Direct and Indirect Effect of TNFα and IFNγ Toward Apoptosis in Breast Cancer Cells - Wahyu Widowati; Diana Krisanti Jasaputra; Sutiman Bambang Sumitro; Mochammad Aris Widodo; Ervi Afifah; Rizal Rizal; Dwi Davidson Rihibiha; Hanna Sari Widya Kusuma; Harry Murti; Indra Bachtiar; Ahmad Faried (Cell and BioPharmaceutical Institute, 2018)
Background: Breast cancer (BC) is the leading cause of death cancer in women. Cancer therapies using TNFα and IFNγ have been recently developed by direct effects and activation of immune responses. This study was performed to evaluate the effects of TNFα and IFNγ directly, and TNFα and IFNγ secreted by Conditioned Medium-human Wharton’s Jelly Mesenchymal Stem Cells (CM-hWJMSCs) toward apoptosis of BC cells (MCF7).Materials and Methods: BC cells were induced by TNFα and IFNγ in 175 and 350ng/mL, respectively. CM-hWJMSCs were produced by co-culture hWJMSCs and NK cells that secreted TNFα, IFNγ, perforin (Prf1), granzyme B (GzmB) for treating BC cells. The BC cells were treated with CM-hWJMSCs in 50%. The expression of apoptotic genes Bax, p53, and the antiapoptotic gene Bcl-2 were determined using RT-PCR.Results: TNFα and IFNγ at concentration of 350 ng/mL induced higher Bax expression compared to 175 ng/mL. TNFα and IFNγ 350 ng/mL, 175 ng/mL induced p53 expression, whilst TNFα and IFNγ at 350 ng/mL decreased Bcl-2 expression. Perf1, GzmB, TNFα and IFNγ-containing CM-hWJMSCs induced significantly apoptosis percentage, induced Bax expression, but did not effect p53, Bcl-2 expression.Conclusion: TNFα and IFNγ directly induce Bax, p53, decrease Bcl-2 gene expression. The Prf1, GzmB, TNFα, IFNγ-containing CM-hWJMSCs induce apoptosis and Bax expression.Keywords: breast cancer, Wharton’s Jelly mesenchymal stem cells, TNFα, IFNγ